Membangun Komunikasi yang Sehat antara Orang Tua dan Anak (Kajian Qur’an Surat Yusuf ayat 4-5) - Syam'un, Fitriyah (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
Values and norms can be conveyed and instilled through healthy communication between parents and children, thereby fostering positive mental qualities in children. That is why creating healthy communication between parents and children is important, as it plays a role in children's growth and development. How can parents build such communication to create healthy communication between parents and children? Here, the author refers to the story of communication between Jacob and Joseph, as mentioned in the Quran, Surah Yusuf, verses 4-5. How does Islam regulate healthy communication between parents and children through the story of Yusuf in the Quran? Research findings indicate that there are many values of healthy communication between parents and children that the Quran presents from the story of Jacob with little Joseph. Among these are the communication methods employed by Jacob as. toward Jospeh, which are characterized by kind, gentle, and calm words and language, speaking while considering and respecting the child’s feelings, and engaging in open and equal communication. These values can be derived from the story of Jacob as. with little Joseph as. depicted in Surah Yusuf, verses 4-5.